2023
DOI: 10.7554/elife.80466
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the rhythms of human activity in the built environment for airborne transmission risk: An analysis of large-scale mobility data

Abstract: Background: Since the outset of the COVID-19 pandemic, substantial public attention has focused on the role of seasonality in impacting transmission. Misconceptions have relied on seasonal mediation of respiratory diseases driven solely by environmental variables. However, seasonality is expected to be driven by host social behavior, particularly in highly susceptible populations. A key gap in understanding the role of social behavior in respiratory disease seasonality is our incomplete understanding of the se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Since the onset of the COVID-19 pandemic, mobile phone data has played a crucial role in addressing the public health crisis [27, 38, 35, 32, 20, 26, 34, 22, 43, 40, 29, 21, 19, 18]. During this period, numerous network operators and private enterprises have made considerable efforts to swiftly share their data within the confines of legal regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the COVID-19 pandemic, mobile phone data has played a crucial role in addressing the public health crisis [27, 38, 35, 32, 20, 26, 34, 22, 43, 40, 29, 21, 19, 18]. During this period, numerous network operators and private enterprises have made considerable efforts to swiftly share their data within the confines of legal regulations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that SARS-CoV-2 transmission is seasonally varying, modulated by environmental variables and environmentally-mediated social behavior [ 24 27 ]. We integrated seasonality in the regional transmissibility (see Model subsection) based on estimates provided in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have suggested that SARS-CoV-2 transmission is seasonally varying, modulated by environmental variables and environmentally-mediated social behavior [25][26][27][28] . We integrated seasonality in the regional transmissibility (see Model subsection) based on estimates provided in Ref.…”
Section: Seasonalitymentioning
confidence: 99%